Growth factors derived from platelet and its applications in regenerative medicine. Potential use of ozone as activator (Ozone Therapy Global Journal, 2011)
A n ewer treatment, autologous p l a telet - r ich plas ma (PRP), r e presents a gre a tersim i l arity to the n atura l healing process as a composite of multiple growt h f actors ,is safe due to its autologous nature, and is produced as needed from patient blood.PPR is an concentration of platelets and growth factors, including transforming growthfactor-beta (TGF-b), vascular endothelial growth factor (VEGF), and platelet derivedgrowth facto r (PDGF). The enhancement of tis sue h e a ling by the placeme n t ofsupr aphysi o l o g ic conc e n tration of autologous p latel e ts at the site of tissue inj u r yor s u r g e r y i s su p p o r ted by bas i c science and c linical studies. Due to the increasedconcentration and release of these factors, PPR can potentially enhance the recruitmentand proliferation of s tem cells and endothel i a l cell s. O zone can pr o mote plateletaggrega tio n a n d release of grow f a ctors wi th both m it o g enic and c h e motac ti cproper tie s. In additio n t o us e in the t r eat ment o f chro n ic skin a nd sof t ti ssueulcera ti o ns , a ppli ca ti o n of thi s method includ e per i odontal and o ral s u rgery,maxillofacial surgery, ortho pedic an d trauma surgery, cos metic and plastic surgery,spina l surgery, heart by pass surgery, and burns. A bette r understanding of pla teletfunction and appropriate clinical use is essential in achieving the desired outcomes ofplatelet-rich concentrate in clinical applications.